JUGUN IANFU : DERITA PEREMPUAN DALAM PUSARAN PERANG - Titik Suliyati (Diponegoro University, 2018)
(Title: Jugun Ianfu: Woman Suffering In War). The formation of the Jugun Ianfu system was motivated by the war in the context of the Japanese military invasion of other countries. The war has made the physical and mental exhaustion of the Japanese army. This condition resulted in the Japanese army carrying out sexual exploitation brutally by carrying out mass rapes in the territories that were colonized by them. Although Japanese occupation in Indonesia was only 3.5 years, the suffering for Jugun Ianfu lasting forever. Even though most Jugun Ianfu has passed away and the relation between Indonesia and Japan is in a good diplomacy, it does not mean that the events experienced by Jugun Ianfu in the past can be forgotten. The history of Jugun Ianfu can provide pictures that position of women in the past was lower than man and there is no law can protect them. Because there is no legal protection, women are helpless when they experience sexual violence. For this reason, in the present, the government should make legal regulations that to protect women from various violence. In addition, the government is expected to provide the widest opportunity for women to get an education so that in the future women can have advanced thoughts.